Rate of Muscle Contraction Is Associated With Cognition in Women, Not in Men - Tian, Qu (J Gerontol A Biol Sci Med Sci, 2019)
BACKGROUND: In older persons, lower hand grip strength is associated with poorer cognition. Little is known about how the rate of muscle contraction relates to cognition and upper extremity motor function, and sex differences are understudied. METHODS: Linear regression, adjusting for age, race, education, body mass index, appendicular lean mass, and knee pain, assessed sex-specific cross-sectional associations of peak torque, rate of torque development (RTD), and rate of velocity development (RVD) with cognition and upper extremity motor function. RESULTS: In men (n = 447), higher rate–adjusted peak torque and a greater RVD were associated with faster simple finger tapping speed, and a greater RVD was associated with higher nondominant pegboard performance. In women (n = 447), higher peak torque was not associated with any measures, but a greater RTD was associated with faster simple tapping speed and higher language performance, and a greater RVD was associated with higher executive function, attention, memory, and nondominant pegboard performance. In women with low isokinetic peak torque, RVD was associated with attention and memory. CONCLUSIONS: RVD capacity may reflect neural health, especially in women with low muscle strength.